Zein hydrolysate and its peptides exert anti-inflammatory activity on endothelial cells by preventing TNF-α-induced NF-κB activation. (January 2020) - Liang, Qiufang; Chalamaiah, Meram; Liao, Wang; Ren, Xiaofeng; Ma, Haile; Wu, Jianping
Graphical abstract: Highlights: Zein derived peptides show anti-inflammatory activity in endothelial cells. Zein derived peptides can inhibit the adhesion of monocytes to endothelial cells. Zein derived ppetides can also inhibit the activation of the NF-κB pathway. Abstract: Vascular inflammation and oxidative stress are the major causes of endothelial dysfunction leading to cardiovascular disease. Previously, we have reported the anti-inflammatory activity of zein hydrolysate and its-derived peptides. However, the underlying mechanisms have not been understood. In this study, we report that zein hydrolysate and its derived peptides can inhibit the tumor necrosis factor-α (TNF-α)-induced expression of intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1), the adhesion of U937 cells to EA.hy926 cells and superoxide production in EA.hy926 cells. Zein hydrolysate and its peptides also suppressed TNF-α-induced down-regulation of TNF receptor 1 (TNFR1) and phosphorylation of p65 involved in modulation of the NF-κB pathway. Our study suggests that zein hydrolysate and its derived peptides exhibited anti-inflammatory activity via preventing TNF-α induced monocyte adhesion to endothelial cells and NF-κB activation.